2015
DOI: 10.1039/c4ob02507e
|View full text |Cite
|
Sign up to set email alerts
|

Thiophene-based dyes for probing membranes

Abstract: We report the synthesis of four new cationic dipolar push-pull dyes, together with an evaluation of their photophysical and photobiological characteristics pertinent for imaging membranes by fluorescence and second harmonic generation. All four dyes consist of an N,N-diethylaniline electron-donor conjugated to a pyridinium electron-acceptor via a thiophene bridge, with either vinylene (-CH=CH-) or ethynylene 10 (-CC-) linking groups, and with either singly-charged or doubly-charged pyridinium terminals. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…We used three previously reported fluorescence sensors of lipid organisation (Chart 1): a pyrene-based dye (PA), 13 di-4-ANEPPDHQ 30 and molecular rotor 2 , which was previously shown to selectively stain the plasma membranes of eukaryotic cells 24,31 and is characterised by equal partitioning of the L d and L o phases of model lipid bilayers. We recently used the phasor analysis 32 of the fluorescence decays of 2 which indicated that 2 detects both L o and L d domains in the plasma membranes of live eukaryotic cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used three previously reported fluorescence sensors of lipid organisation (Chart 1): a pyrene-based dye (PA), 13 di-4-ANEPPDHQ 30 and molecular rotor 2 , which was previously shown to selectively stain the plasma membranes of eukaryotic cells 24,31 and is characterised by equal partitioning of the L d and L o phases of model lipid bilayers. We recently used the phasor analysis 32 of the fluorescence decays of 2 which indicated that 2 detects both L o and L d domains in the plasma membranes of live eukaryotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of 1a , 16 1b , 23 2   31 and PA 13 has been reported previously, while di-4-ANEPPDHQ was obtained from Thermo Fisher Scientific. All solvents used were spectroscopic grade.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical planarization of the twisted push‐pull probe 3 in the ground state causes the excitation maxima to shift to the red. This differs conceptually from other membrane probes that operate by deplanarization (molecular rotors), polarization (solvatochromism) and electron or proton transfer in the excited state and thus report in emission rather than excitation . The resulting flipper probes 3 are important because they provide access to the so far elusive imaging of forces such as membrane tension in living cells (unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…The application of this more complex lesson from nature to fluorescent probes has received little attention so far. However, a combination of planarization and polarization in the ground state appeared most intriguing, particularly with regard to fluorescent probes that could report on key characteristics of biomembranes such as fluidity, potential as well as the so far elusive membrane tension …”
Section: Introductionmentioning
confidence: 99%